Nilpotent centers from analytical systems on center manifolds - Pessoa, Claudio [UNESP] (2023)
Consider analytical three-dimensional differential systems having a singular point at the origin such that its linear part is y∂x−λz∂z for some λ≠0. The restriction of such systems to a Center Manifold has a nilpotent singular point at the origin. We prove that if the restricted system is analytic and has a nilpotent center at the origin, with Andreev number 2, then the three-dimensional system admits a formal inverse Jacobi multiplier. We also prove that nilpotent centers of three-dimensional systems, on analytic center manifolds, are limits of Hopf-type centers. We use these results to solve the center problem for some three-dimensional systems without restricting the system to a parametrization of the center manifold.